Forced Cultivation System and the Cultural Response of the Cirebon Society, West Java, (1830-1850) - Muhammad Faishal Amir Fauzi; Lani Febriyanti; Fuadul Umam; Affan Ismail; Moh. Ashif Fuadi (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
This study examines the impact of the forced cultivation policy in the Cirebon Residency between 1830 and 1850, focusing on the social dynamics and cultural responses of the local community. This system compelled villagers to cultivate export commodities such as coffee, sugarcane, and indigo, replacing traditional subsistence farming. This study aims to provide a historical account of the implementation of the forced cultivation system and to analyze how the people of Cirebon responded to colonial pressure through adaptation, symbolic resistance, and the transformation of traditional values. This study employs a qualitative historical approach using historical research methods to analyze the implementation of the forced cultivation system in the Cirebon Residency during the period 1830–1850. The results of the study indicate that the implementation of forced cultivation not only impacted the economic structure in Cirebon but also eroded social solidarity, reinforced the dominance of the local elite, and triggered a humanitarian crisis at the grassroots level. Nevertheless, the people of Cirebon succeeded in preserving their cultural values and identity through strategies of cultural adaptation, the preservation of collective rituals, and symbolic resistance in the form of art, folklore, and spiritual practices.